Recruiting higher education students: a systematic review of the college selection process models - Sia, Joseph (Inderscience, 2011)
The study of student enrolment decision-making or college choice behaviour is an extremely practical operation that leads to greater efficiency and effectiveness. Understanding student college choice behaviour enables institutions of higher learning to estimate the probability of student interest and enrolment. Higher education institutions (HEIs) would be able to strategise their marketing efforts in the scramble for students. This paper seeks to review systematically the student college choice models. The models to be reviewed are Chapman model (1981), Hanson and Litten model (1982), Jackson model (1982) and Hossler and Gallagher model (1987). It is suggested that future research should investigate on ‘campus security’ on student decision making in college enrolment as it has not been empirically studied in the models abovementioned. Furthermore, future empirical research can also be carried out on prospective students, i.e., students who have yet to enrol in HEI in Southeast Asia countries.